Register Now

222-9+11+12:2*14+14 = ? ( )

## Toán Lớp 9: a) (2x-1)(x+7)=x^2-49 b)2x+1/x-3 – x/x+3 =1 c)x+2/3-3x-1/5<-2

Toán Lớp 9: a) (2x-1)(x+7)=x^2-49 b)2x+1/x-3 – x/x+3 =1 c)x+2/3-3x-1/5<-2

## Comments ( 2 )

1. Giải đáp + Lời giải và giải thích chi tiết:
a)
(2x-1)(x+7)=x^2-49
<=> (2x-1)(x+7)-(x^2-49)=0
<=> (2x-1)(x+7)-(x-7)(x+7)=0
<=> (x+7)(2x-1-x+7)=0
<=> (x+7)(x+6)=0
<=> $$\left[ \begin{array}{l}x+7=0\\x+6=0\end{array} \right.$$ <=> $$\left[ \begin{array}{l}x=-7\\x=-6\end{array} \right.$$
Vậy S={-7;-6}
b)
(2x+1)/(x-3)-x/(x+3)=1
ĐKXĐ : x ne +-3
<=> ((2x+1)(x+3)-x(x-3))/(x^2-9)=(x^2-9)/(x^2-9)
=> (2x+1)(x+3)-x(x-3)=x^2-9
<=> 2x^2+6x+x+3-x^2+3x-x^2+9=0
<=> 10x+12=0
<=> 10x=-12
<=> x=-6/5 \ \ (tmđk)
Vậy S={-6/5}
c)
(x+2)/3-(3x-1)/5<-2
<=> (5.(x+2)-3.(3x-1))/15< -30/15
=> 5.(x+2)-3.(3x-1)=-30
<=> 5x+10-9x+3<-30
<=> -4x<-30-3-10
<=> -4x<-43
<=> x>43/4
Vậy S={x|x>43/4}

2. a)(2x-1)(x+7)=x²-49
⇔(2x-1)(x+7)=(x+7)(x-7)
⇔(2x-1)(x+7)-(x+7)(x-7)=0
⇔(x+7)[(2x-1)-(x-7)]=0
⇔(x+7)(2x-1-x+7)=0
⇔(x+7)(x+6)=0
$$\left[ \begin{array}{l}x+7=0\\x+6=0\end{array} \right.$$
⇔$$\left[ \begin{array}{l}x=-7\\x=-6\end{array} \right.$$
Vậy S={-7;-6}
b)(2x+1)/(x-3)-x/(x+3)=1(ĐKXĐ:x$\neq$ ±3)
⇔[(2x+1)(x+3)]/[(x+3)(x-3)]-[x(x-3)]/[(x+3)(x-3)]=[(x+3)(x-3)]/[(x+3)(x-3)]
⇒(2x+1)(x+3)-x(x-3)=(x+3)(x-3)
⇔2x²+6x+x+3-x²+3x=x²-9
⇔(2x²-x²)+(6x+x+3x)+3=x²-9
⇔x²+10x+3=x²-9
⇔x²+10x-x²=-9-3
⇔10x=-12
⇔x=-12/10
⇔x=-6/5(TM ĐKXĐ)
Vậy S={-6/5}
c)(x+2)/3-(3x-1)/5<-2
⇔[5(x+2)]/15-[3(3x-1)]/15<-30/15
⇒5(x+2)-3(3x-1)<-30
⇔5x+10-9x+3<-30
⇔5x-9x<-30-10-3
⇔-4x<-43
⇔x>43/4
Vậy S={x|x>43/4}